2016
DOI: 10.1002/eco.1728
|View full text |Cite
|
Sign up to set email alerts
|

Importance of soil‐water to the Caatinga biome, Brazil

Abstract: Northeastern Brazil is hydrologically characterized by recurrent droughts leading to a highly vulnerable natural water resource system. The region contains the Caatinga biome, covering an area of approximately 800 000 km 2 . To increase insight in water balance components for this sparsely studied ecosystem, hydrology simulations were performed with the SWAP (Soil Water Atmosphere Plant) model for a Caatinga basin of 12 km 2 . SWAP model was developed to simulate hydrology under short-cycle crops, and its para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 56 publications
1
36
0
2
Order By: Relevance
“…Average annual rainfall is 518 mm, concentrated in the rainy season between January and May. The monthly average temperatures range from 24 • C to 28 • C. The watershed is covered by dense native vegetation characterized by tree heights typically between 5 and 12 m. More detailed information can be found in [10,16,17].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Average annual rainfall is 518 mm, concentrated in the rainy season between January and May. The monthly average temperatures range from 24 • C to 28 • C. The watershed is covered by dense native vegetation characterized by tree heights typically between 5 and 12 m. More detailed information can be found in [10,16,17].…”
Section: Study Areamentioning
confidence: 99%
“…The water table is located several meters below the river bed, restraining its connection to the root zone, and rainfall is the main source of water for plant transpiration. Consequently, the Caatinga forest developed shallow roots to enhance root water uptake from upper soil layers [10,11]. Leaf shedding is the main characteristic and survival strategy to cope with up to nine months of the rainless season.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research carried out in the Brazilian semi-arid region demonstrated the importance of the soil both in the surface flow initiation and as a water reservoir for vegetation (FIGUEIREDO et al 2016;PINHEIRO et al 2016). Most studies indicate the surface reservoirs as the main water container within a watershed (DE ARAUJO et al, 2004;MALVEIRA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As regards arid and semi-arid ecosystems, soil water is of utmost importance to biogeochemical cycles and recycling nutrients (WANG 2012). In addition, it must be considered that the water strongly interacts with atmospheric processes, e.g., evapotranspiration, air temperature and rainfall (SENEVIRATNE et al 2010;PINHEIRO et al 2016).…”
Section: Introductionmentioning
confidence: 99%